Salvage high-dose-rate brachytherapy for histologically confirmed macroscopic local relapsed prostate cancer after radical prostatectomy - Buchser, David; Gomez-Iturriaga, Alfonso; Melcon, J. Ignacio Rodriguez; Casquero, Francisco; Llarena, Roberto; Cacicedo, Jon; Bilbao, Pedro (Journal of Contemporary Brachytherapy, 2016)
Purpose: To evaluate the feasibility of the use of real-time magnetic resonance imaging (MRI)-transrectal ultrasound (TRUS) fusion guided high-dose-rate brachytherapy (HDR-BT) +/– external beam radiation therapy (EBRT) in patients with histologically-proven local relapse after radical prostatectomy. Material and methods : We retrospectively reviewed 13 patients treated with real-time MRI-TRUS fusion HDR-BT for a local relapse of prostate cancer after radical surgery. All patients underwent multiparametric magnetic resonance imaging (mpMRI) to confirm the presence of macroscopic lesions in prostate bed, and choline positron emission tomography/computed tomography (PET/CT) to rule out nodal or distant metastases. Local failure was confirmed by transrectal biopsy. Patients without previous EBRT received 1 fraction of 15 Gy with HDR-BT plus hypofractionated EBRT (37.5 Gy in 15 fractions). Two patients received 2 fractions of 12 Gy with HDR-BT without EBRT. Follow-up visits were at 1, 3, 6 months, and every 6 months thereafter. Results : After a median follow-up of 7 months, all patients showed an appropriate biochemical response. Median prostate-specific antigen (PSA) levels before treatment, 1 month, and 6 months after HDR-BT were 2.62 ng/ml (range: 1.55-9.61), 0.97 ng/ml (range: 0.12-3.14), 0.23 ng/ml (range: 0.1-0.74), respectively. Five patients (42%) experienced acute grade 1 GU toxicity and 1 patient (8%) suffered from grade 2 GU toxicity. Regarding gastrointestinal (GI) toxicity, 5 patients referred grade 1 acute toxicity and 1 grade 2 (proctitis). No late toxicity has been observed so far. Conclusions : MRI-TRUS fusion guided salvage HDR-BT +/– EBRT is a feasible procedure for patients with local macroscopic relapse in tumor bed after radical prostatectomy. Exquisite selection of patients through mpMRI and choline PET/CT is crucial to avoid overtreatment. A larger number of patients and longer follow-up are required in order to draw more solid conclusions regarding the effectiveness of this strategy.